2015
DOI: 10.1371/journal.pone.0123003
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant Hamster Oviductin Is Biologically Active and Exerts Positive Effects on Sperm Functions and Sperm-Oocyte Binding

Abstract: Studies carried out in several mammalian species suggest that oviductin, also known as oviduct-specific glycoprotein or OVGP1, plays a key role in sperm capacitation, fertilization, and development of early embryos. In the present study, we used recombinant DNA technology to produce, for the first time, recombinant hamster OVGP1 (rHamOVGP1) in human embryonic kidney 293 (HEK293) cells. rHamOVGP1 secreted in the culture medium was purified by affinity chromatography. The resulting protein migrated as a poly-dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 57 publications
2
37
0
Order By: Relevance
“…We observed that the dMLL3/4-regulated glycosyl hydrolase IDGF4 has a mitogenic effect on the early embryo. Despite being important for fertilization and early embryogenesis across different mammalian species, the exact function of OVGP1 remains elusive [52]. OVGP1 localizes to the oviduct-the site of mammalian fertilization-where it has been shown to be a component of the extracellular matrix of ovulated oocytes and early embryos [50,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We observed that the dMLL3/4-regulated glycosyl hydrolase IDGF4 has a mitogenic effect on the early embryo. Despite being important for fertilization and early embryogenesis across different mammalian species, the exact function of OVGP1 remains elusive [52]. OVGP1 localizes to the oviduct-the site of mammalian fertilization-where it has been shown to be a component of the extracellular matrix of ovulated oocytes and early embryos [50,51].…”
Section: Discussionmentioning
confidence: 99%
“…OVGP1 localizes to the oviduct-the site of mammalian fertilization-where it has been shown to be a component of the extracellular matrix of ovulated oocytes and early embryos [50,51]. Despite being important for fertilization and early embryogenesis across different mammalian species, the exact function of OVGP1 remains elusive [52]. Accordingly, OVGP1 has been associated with processes as wide-ranging as sperm capacitation and blastocyst formation [53][54][55].…”
Section: Discussionmentioning
confidence: 99%
“…Immediate and dramatic control of sperm physiology within the oviduct can be exerted by local concentrations of small molecules such as bicarbonate [103], calcium, [104,105] and nitric oxide [106] as well as by secreted proteins [107]. However, there is little to suggest at present that these effects are preferentially exerted on sperm subpopulations with specific genetic properties.…”
Section: Can the Oviduct Distinguish The Genetic Properties Of Spermamentioning
confidence: 99%
“…However, only a few ODF proteins, in particular glycoproteins, such as oviduct‐specific glycoprotein (OVGP1), have been utilized as potential supplements to support and/or control the in vitro processes that precede fertilization . Supplementation of the media with recombinant OVGP1 modulates human and hamster spermatozoa capacitation in vitro. Likewise, lactoferrin (LTF) might be added to promote the capacitation of spermatozoa …”
Section: Introductionmentioning
confidence: 99%